Model Metode Asuhan Keperawatan Profesional (MAKP) Tim Berbasis Structural Empowerment terhadap Kualitas Kehidupan Kerja Perawat - Yulianti, Maria Goretti; Triharini, Mira; Wahyudi, Andri Setiya (Journal of Telenursing (JOTING), 2024)
This research aims to develop an effective Team MAKP model to improve the quality of nurses' work life using a structural empowerment approach. The method used is a systematic review by collecting articles using the Scopus, Science Direct, Proquest and PubMed databases, to search for keywords using the Medical Subject Headings (MeSH) system related to relevant articles in this research. Initial research results produced 547 articles (Scopus, Science Direct, Proquest Pubmed and Google Scholar). Articles were narrowed down based on the last 5 years and did not include literature reviews and 127 articles were filtered. Articles with completeness assessed for article suitability were 29 articles. The final results of the 16 articles analyzed show that team MAKP with a structural empowerment approach can help improve the quality of nurses work life. The conclusion of this research is that the results of the systematic review provide it was found that the MAKP Team was able to provide quality work life for nurses with a structural empowerment approach. Explain empowerment in the care unit, especially the climate within the care team with structural empowerment, so that nurses/team members and team leaders feel satisfied with their work experience. Keywords: Quality of Work Life, Team MAKP,Nurse, Structural Empowerment.